Assessment of the Nurses Practices Toward Care the Child with Clubfoot at the Orthopedic Units at Baghdad City - Raad Hassan Kshaish, Khalida A. Mansur, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective(s): To improve the nurses' practice who working in the orthopedic units towards care the child with clubfoot and to find the relationship between the nurses' practices and their demographic characteristics. Methodology: A descriptive study was conducted at three teaching hospitals (Al-Kindi Teaching Hospital, Al-Wasiti Teaching Hospital and the Child welfare Teaching Hospital for the period from 17th of February to 2th of March of 2023. A non-probability sample had (60) nurses who working at the orthopedic units (included outpatient clinics, orthopedic wards and braces units). The pilot study performed for the period from 5th to 15th of February to 2023 on 6 nurses to test the reliability and applicability of the study tool and to determine the time consuming for doing it. The study tool constructed based on previous literatures related to the current study which included a nurses' socio demographic characteristics in part one while the second part as observational checklists in four domains. The data analyze through the spss program version (26) to interpret and explain the results of the study. Results: The results of the study showed the most (75%) of the nurses' practices in all domains were at low level (M.S less than 0.33) In regarding their demographic characteristics; the most (70%) of them were females, (40%) of them were within the age group (30-40 years) and 57.4% of them had a diploma in nursing. Conclusions: The study concluded that the studied nurses had an adequate practice regarding care of a child with clubfoot at the orthopedic units. While there on statistically significant relationship between the socio-demographic characteristics of the nurses and their nurses' practice. Keywords: Effectiveness, Clinical pathway program, Clubfoot, Child, Nurses’ Practices, Orthopedic units.